Uterine arteriovenous malformation treated with selective embolisation of uterine arteries: a case report - Rudaitis, Vilius; Maldutytė, Gailė (Acta medica Lituanica, 2021)
Uterine arteriovenous malformation (AVM) is a very rare gynaecological condition, which can potentially lead to life-threatening abnormal uterine bleeding. In most cases uterine AVM is associated with prior pregnancy or pelvic surgery. We present the case of young woman seven weeks after medical termination of pregnancy diagnosed with heavy uterine bleeding due to uterine AVM, which was successfully treated with selective embolisation of uterine arteries.